2017
DOI: 10.1504/emjm.2017.084273
|View full text |Cite
|
Sign up to set email alerts
|

Developing strategic relationships for religious tourism businesses: a systematic literature review

Abstract: The purpose of this paper is to systematically analyse the existing literature on the interrelationships of tourism businesses in the context of religious tourism. By taking a systematic approach to literature review, a total of 34 academic articles was content analysed. As a general framework, Watkins and Bell's classification was applied in order to increase the review consistency and validity. The results show that the inter-relationships of tourism businesses have gained an increasing academic attention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…So far, SLRs in the field of sport tourism have focused on this field's combination with sustainability issues [137][138][139], mobile technologies [140], and services [141] or engaged with a general knowledge agenda [142][143][144]. Multiple studies in tourism research conducting an SLR have followed various approaches; however, the basic content stays the same [145][146][147][148][149][150][151][152]. This paper uses a four-step approach (Figure 4).…”
Section: Methodology: Systematic Literature Reviewmentioning
confidence: 99%
“…So far, SLRs in the field of sport tourism have focused on this field's combination with sustainability issues [137][138][139], mobile technologies [140], and services [141] or engaged with a general knowledge agenda [142][143][144]. Multiple studies in tourism research conducting an SLR have followed various approaches; however, the basic content stays the same [145][146][147][148][149][150][151][152]. This paper uses a four-step approach (Figure 4).…”
Section: Methodology: Systematic Literature Reviewmentioning
confidence: 99%
“…The first flow addresses the use of network analysis to understand the evolution of business networks and to analyze interorganizational relationships. For example, Heidari et al (2017) found that the interrelationships of tourism businesses have gained an increasing academic attention in the past decade. They argued that the various categories of interorganizational relationships of tourism businesses have been used in relation to tourism business.…”
Section: Network Analysis In Tourismmentioning
confidence: 99%
“…Therefore, industrial tours and exhibitions can be regarded as the basis of industrial tourism. Governmental managers, private sector industrialists, engineers, students as well as research- and knowledge-based entities could have various economic interactions with well-known foreign brands through these specialized tours (Heidari et al , 2017). They can also be familiar with new technologies and industrial equipments which in turn, led to a number of economic agreements between Iran and the industrialized countries such as Italy and Germany (Doosti et al , 2016).…”
Section: Introductionmentioning
confidence: 99%